Descriptive study of cleft lip and palate related to individual, systemic and social factors - Thiago Machado Ardenghi; Luciana Butini Oliveira; Lucy Dalva Lopes Mauro; Dalysse Salles Freitas e Silva; Marcelo Bonecker (Faculdade São Leopoldo Mandic, 2008)
Objectives: Verify the types of fissures that most affect patients under 12 years of age, at the Facial Deformity Rehabilitation Center in São Paulo, and evaluate individual, systemic and social factors.Methods: A sample of 100 children and adolescents with cleft lip and palate were selected with the purpose of collecting data as regards sex, race, type of fissure and side affected, syndromes, sequences and associated malformations, presence of family history of fissure, and age of parents at the time of the child's conception. The patients' parents answered a previously validated questionnaire with closed questions to provide data as regards the socio-economic factor. All the information was stored in a database and submitted to descriptive statistical analysis. Results: 61% of population sample was of the male gender and 92% was of the white race. The incisive trans-foramen fissure was prevalent (62%) and the unilateral fissures were most frequent (65.8%), and the left side was the most affected (44.3%). As regards systemic factors, 22% of the patients had syndromes or sequences; the most frequently associated syndrome was the Pierre Robin. Among the malformation associated with cleft lip and palate fissures, congenital heart diseases were prevalent (37.9%). Family recurrence of fissures was shown in only 23% of cases. The family nuclei were composed of married parents (84%), who had higher education (47%) and worked full time (81%). Conclusion: There was greater frequency of the incisive trans-foramen fissure and greater occurrence in the male gender. Congenital heart diseases and the Pierre Robin sequence were the syndromes most frequently associated with cleft lip and palate. There was no family tendency towards cleft lip and palate fissures, and the majority of families were in a good socio-economic and educational condition.